2005
DOI: 10.1002/med.20026
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of kinase-biased compounds in the search for lead inhibitors of kinase targets

Abstract: This work describes the preparation of approximately 13,000 compounds for rapid identification of hits in high-throughput screening (HTS). These compounds were designed as potential serine/threonine or tyrosine kinase inhibitors. The library consists of various scaffolds, e.g., purines, oxindoles, and imidazoles, whereby each core scaffold generally includes the hydrogen bond acceptor/donor properties known to be important for kinase binding. Several of these are based upon literature kinase templates, or adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It was demonstrated that depending on the type of the immobilization strategy, the target purines could be simply diversified at positions 2, 6, 8, and 9 using readily available starting materials. This fact led to the application of combinatorial solid-phase synthesis to produce and study collections of desired compounds, with CDK inhibitor libraries being the well-known examples. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was demonstrated that depending on the type of the immobilization strategy, the target purines could be simply diversified at positions 2, 6, 8, and 9 using readily available starting materials. This fact led to the application of combinatorial solid-phase synthesis to produce and study collections of desired compounds, with CDK inhibitor libraries being the well-known examples. …”
Section: Introductionmentioning
confidence: 99%
“…The method of immobilization is the key aspect of solid-phase synthesis because it typically limits the resulting diversification possibilities. Although positions C 6 and N 9 have been identified as the most suitable for this purpose, 10−13 a detailed literature survey revealed that the strategies for immobilization via any other position are available, except for the quaternary carbon atoms C 4 and C 5 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is likely that pharmaceutical companies will continue to produce interesting data using legacy libraries of unpurified reaction mixtures. With reported library hit rates in the range of 0.1% to 1%, 6 it is less expensive to reserve purification initially for those reaction mixtures whose activities reconfirm and then for any focused libraries subsequently produced around the active series.…”
Section: Introductionmentioning
confidence: 99%